Immune Checkpoint Molecules on Tumor-Infiltrating Lymphocytes and Their Association with Tertiary Lymphoid Structures in Human Breast Cancer - Solinas, Cinzia; Garaud, Soizic; De Silva, Pushpamali; Boisson, Anaïs; Van den Eynden, Gert; de Wind, Alexandre; Risso, Paolo; Rodrigues Vitória, Joel; Richard, François; Migliori, Edoardo; Noël, Grégory; Duvillier, Hugues; et al. (Frontiers in Immunology, 2017)
There is an exponentially growing interest in targeting immune checkpoint molecules in breast cancer, particularly in the triple-negative subtype where unmet treatment needs remain. This study was designed to analyze the expression, localization and prognostic role of PD-1, PD-L1, PD-L2, CTLA-4, LAG3 and TIM3 in primary breast cancer. Gene expression analysis using the METABRIC microarray dataset found that all six immune checkpoint molecules are highly expressed in basal-like and HER2-enriched compared to the other breast cancer molecular subtypes. Flow cytometric analysis of fresh tissue homogenates from untreated primary tumors show that PD-1 is principally expressed on CD4+ or CD8+ T cells and CTLA-4 on CD4+ T cells. The global proportion of PD-L1+, PD-L2+, LAG3+ and TIM3+ tumor infiltrating lymphocytes was low and detectable in only a small number of tumors. Immunohistochemically staining fixed tissues from the same tumors was employed to score tumor infiltrating lymphocytes and tertiary lymphoid structures. PD-L1+, PD-L2+, LAG3+ and TIM3+ cells were detected in some tertiary lymphoid structures in a pattern that resembles secondary lymphoid organs. This observation suggests that tertiary lymphoid structures are important sites of immune activation and regulation, particularly in tumors with extensive baseline immune infiltration. Significantly improved overall survival was correlated with PD-1 expression in the HER2-enriched and PD-L1 or CTLA-4 expression in basal-like breast cancer. PD-1 and CTLA-4 proteins were most frequently detected on tumor infiltrating lymphocytes, which supports the correlations observed between their gene expression and improved long term outcome in basal-like and HER2-enriched breast cancer. PD-L1 expression by tumor or immune cells is uncommon in breast cancer. Overall, the data presented here distinguish PD-1 as a marker of T cell activity in both the T and B cell areas of breast cancer associated tertiary lymphoid structures. We found that immune checkpoint molecule expression parallels the extent of tumor infiltrating lymphocytes and tertiary lymphoid structures, although there is a noteworthy amount of heterogeneity between tumors even within the same molecular subtype. These data indicate that assessing the levels of immune checkpoint molecule expression in an individual patient has important implications for the success of therapeutically targeting them in breast cancer.